Optimalisasi Financial Teknologi (Fintech) terhadap Peningkatan Literasi dan Inklusi Keuangan Usaha Menengah Purwokerto - Cut Misni Mulasiwi; Karina Odia Julialevi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2020)
The purpose of this study is to explain the effect of fintech-based financial services on financial literacy and financial inclusion on Medium Enterprises in Purwokerto. To test the empirical model, Structural Equation Modeling (SEM) analysis was used. Other analysis tools used included AMOS 21.0, SPSS 16.0 and Microsoft Excel 2010. The number of samples in this study was 108 micro business owners. The results of this study indicate that fintech-based financial services have a positive influence on financial literacy and micro-business financial inclusion in Purwokerto.